PHYSICAL ACTIVITY AND SPORTS IN PATIENTS WITH EPILEPSY - Odintsova, G.V.; Koloteva, A.V.; Lovyagina, A.E. (Malang Neurology Journal, 2020)
Background: For many years, patients with epilepsy have been strongly advised to avoid sports and exercise, as it was believed that sporting activities can trigger seizures.Objective: To study the level of physical and sporting activity on the example of the patients of the Russian Epilepsy Center.Methods: The study includes 50 patients with a verified diagnosis of epilepsy. The survey has been conducted according to a specially developed questionnaire